Reactions, reactivity, rampant reductions: on self-fulfilling prophecies, the Matthew effect, and global potentials of a new gallery ranking - Buckermann, Paul (Creative industries journal, 2018)
This essay discusses functions and structural consequences of quantifying rankings as a rather new phenomenon in the art worlds. Focused on a new list of galleries for contemporary art in France, the text uses sociological findings to reflect on direct reactions towards the ranking and its inventor. Furthermore, this constructivist perspective indicates potential structural outcomes of publicly communicated comparisons in a globalised art world and its market infrastructure. The discussed gallery ranking contains every communicative potential to trigger self-fulfilling prophecies, homogenised resource distribution or Mathew effects in the field of art galleries. By referring to findings on rankings in other fields, the essay proposes reflecting on effects and mechanisms of assumedly objective measures in the arts and rather analysing them as contingently produced comparisons and epistemic tools.